Ubiquitylome study identifies increased histone 2A ubiquitylation as an evolutionarily conserved aging biomarker. - Yang, L.; Ma, Z.; Wang, H.; Niu, K.; Cao, Y.; Sun, L.; Geng, Y.; Yang, B.; Gao, F.; Chen, Z.; Wu, Z.; Li, Q.; et al. (Nature communications, 2019)
The long-lived proteome constitutes a pool of exceptionally stable proteins with limited turnover. Previous studies on ubiquitin-mediated protein degradation primarily focused on relatively short-lived proteins; how ubiquitylation modifies the long-lived proteome and its regulatory effect on adult lifespan is unclear. Here we profile the age-dependent dynamics of long-lived proteomes in Drosophila by mass spectrometry using stable isotope switching coupled with antibody-enriched ubiquitylome analysis. Our data describe landscapes of long-lived proteins in somatic and reproductive tissues of Drosophila during adult lifespan, and reveal a preferential ubiquitylation of older long-lived proteins. We identify an age-modulated increase of ubiquitylation on long-lived histone 2A protein in Drosophila, which is evolutionarily conserved in mouse, monkey, and human. A reduction of ubiquitylated histone 2A in mutant flies is associated with longevity and healthy lifespan. Together, our data reveal an evolutionarily conserved biomarker of aging that links epigenetic modulation of the long-lived histone protein to lifespan.